Project Management skills (Rugeley : Focus Multimedia Limited, 2005)
The step-by-step guide to getting your project finished on time and on budget.
Ελάχιστες απαιτήσεις συστήματος: Windows 98/Me/2000/XP.
Keywords: Project management -- Computer programs; CD-ROMs.